Synthesis, structure elucidation and antimicrobial activity of some 3-hydroxy-2-naphthoic acid hydrazide derivatives - (:unkn) unknown (My University, 1998)
In this study, some 1,4-disubstituted thiosemicarbazide, 1,2,4-triazole and 1,3,4-thiadiazole type novel compounds derived from 3-hydroxy-2-naphthoic acid hydrazide were synthesized to screen for their antimicrobial activity. The structures of these substances were elucidated using elemental analysis and UV, 1H NMR, and mass spectral methods. All of these compounds were tested in vitro for their antibacterial and antifungal activity.
Keywords: Neoplasms; Microbial Sensitivity Tests; Antifungal Agents; Molecular Structure; Semicarbazides; Anti-Infective Agents; HIV; Structure-Activity Relationship